The pathfinder, or, The inland sea - Cooper, James Fenimore, 1789-1851.; Rust, Richard Dilworth (Albany : State University of New York Press, 1981)
In the sequel to The Last of the Mohicans, Natty Bumppo tries to help a small outpost on Lake Ontario.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Bumppo, Natty -- (Fictitious character); Bumppo, Natty (Fictitious character) -- Fiction; United States -- History -- French and Indian War, 1754-1763 -- Fiction; États-Unis -- Histoire -- 1755-1763 (Guerre de Sept Ans) -- Romans, nouvelles, etc; États-Unis -- Histoire -- 1754-1763 (Guerre de Sept Ans) -- Romans, nouvelles, etc; FICTION -- Historical; United States; 1754-1763; United States -- History -- French and Indian War, 1755-1763 -- Fiction; War stories; War stories; Historical fiction; Fiction; History; War stories; Historical fiction; Historical fiction; Novels